Radiologic common data elements rates in pediatric mild traumatic brain injury. (21st January 2020) - Mayer, Andrew R.; Cohen, Daniel M.; Wertz, Christopher J.; Dodd, Andrew B.; Shoemaker, Jody; Pluto, Charles; Zumberge, Nicholas A.; Park, Grace; Bangert, Barbara A.; Lin, Cindy; Minich, Nori M.; Bacevice, Ann M.; et al.
Abstract : Objective: The nosology for classifying structural MRI findings following pediatric mild traumatic brain injury (pmTBI) remains actively debated. Radiologic common data elements (rCDE) were developed to standardize reporting in research settings. However, some rCDE are more specific to trauma (probable rCDE). Other more recently proposed rCDE have multiple etiologies (possible rCDE), and may therefore be more common in all children. Independent cohorts of patients with pmTBI and controls were therefore recruited from multiple sites (New Mexico and Ohio) to test the dual hypothesis of a higher incidence of probable rCDE (pmTBI > controls) vs similar rates of possible rCDE on structural MRI. Methods: Patients with subacute pmTBI (n = 287), matched healthy controls (HC; n = 106), and orthopedically injured (OI; n = 71) patients underwent imaging approximately 1 week postinjury and were followed for 3–4 months. Results: Probable rCDE were specific to pmTBI, occurring in 4%–5% of each sample, rates consistent with previous large-scale CT studies. In contrast, prevalence rates for incidental findings and possible rCDE were similar across groups (pmTBI vs OI vs HC). The prevalence of possible rCDE was also the only finding that varied as a function of site. Possible rCDE and incidental findings were not associated with postconcussive symptomatology or quality of life 3–4 months postinjury. Conclusion: Collectively, current findings question the trauma-related specificity of certain rCDE, as well how these rCDE are radiologically interpreted. Refinement of rCDE in the context of pmTBI may be warranted, especially as diagnostic schema are evolving to stratify patients with structural MRI abnormalities as having a moderate injury.